(untitled) (International Journal of Physiotherapy, 2019)
Background: Knee pain in general and if to be specific is the pain located anteriorly, and it is widespread among teenage, adults, and the old age population. Among the anterior knee pain etiologies, patellofemoral pain is one of the most common causes of knee pain. One of the significant issues with the patellofemoral pain is that most of the time it is misdiagnosed, or it is underrated for patients’ problems, which in the long run lead to severe functional limitations and muscular atrophy. Right clinical diagnosis at an early phase in musculoskeletal conditions is vital. Case summary: The patient presented with chief complaints of diffused pain over right leg tracking it over to the lower back. She presented with a painful limping gait. No tenderness was noted over the lower back; the neural tension test was nonsignificant. Patellar compression test, Clark’s test, eccentric step was positive. Severe disuse quadriceps muscular atrophy was noted over-involved limb. Tenderness over the retropatellar surface was significant. The patient was managed with cryotherapy at home, therapeutic ultrasound over the tender area along with Kinesio tapping, proprioception exercises, stretching, and strengthening exercises. Outcome measure: Pain, ROM, girth measurement, gait pattern. Significant improvement was noted in pain on NPS, ROM, and gait pattern in two weeks management. Conclusion: The Physiotherapy management in cases of anterior knee pain, specifically patellofemoral pain, mainly consisting of kinesiotaping, therapeutic ultrasound, cryotherapy, therapeutic exercises are very effective provided right clinical diagnosis, is made. The treatment outcome may be more fruitful if the correct clinical diagnosis is made at an early stage.